REINTEGRATION OF RELIGIOUS KNOWLEDGE AND GENERAL KNOWLEDGE (CRITICISM OF THE DISCOURSE OF SCIENCE DICHOTOMY) - Fajar Syarif (Transformatif, 2020)
This article aims to determine the implications that can arise from the dichotomy of science. Namely the emergence of a gap between the source of knowledge in the form of religious knowledge and general knowledge. Proponents of the religious knowledge only consider the divine source valid in the form of scriptures and prophetic traditions and reject non-scriptural sources as an authoritative source to explain true truth. On the other hand, secular scientists only consider valid information obtained through sensory observation. The method used in this study is qualitative with a phenomenological approach. Data collection was conducted through observation, in-depth interviews, documentation analysis and focused group discussion. This research shows that there is really no sorting of science and religion. The research findings provide an overview of science and the knowledge of religion is integral. If science is addressed with a dichotomy, it will certainly give birth to different thoughts in building world civilization.